ANALISIS PENGARUH FAKTOR FUNDAMENTAL, TEKNIKAL DAN MAKRO EKONOMI TERHADAP HARGA SAHAM PADA PERUSAHAAN YANG TERDAFTAR PADA INDEX JII SELAMA MASA PANDEMI COVID-19 - Novita Novita (INSTITUT TEKNOLOGI DAN BISNIS INDOBARU NASIONAL, 2023)
This study aims to examine and analyze the influence of fundamental, technical and macroeconomic factors on stock prices during the Covid-19 pandemic. Variables used in representing fundamental factors include Earnings Per Share (EPS), Return On Equity (ROE), and Debt to Equity Ratio (DER). Technical factors use trading volume, while macroeconomic factors use inflation rate and interest rate variable. The population used in this study are companies whose shares are listed in the Jakarta Islamic Index (JII). The sampling technique uses purposive sampling, while the criteria in sampling are company shares that have consistently entered JII in the last 10 years. The data used in this study used secondary data taken from www.idx.co.id and www.bi.go.id. The analysis model used in this study was multiple regression. The results of the study partially stated that EPS had a significant positive effect on stock prices and ROE had a significant negative effect on stock prices. DER, trading volumes, inflation and interest rates have no significant effect on stock prices. Keywords: fundamental factors, technical factors, macroeconomic factors, stock price fluctuations, Jakarta Islamic Index, COVID-19 pandemic